ISLAM, AGAMA TOLERANSI DAN CINTA DAMAI : (TELAAH ATAS NOVEL AYAT-AYAT CINTA KARYA HABIBURRAHMAN EL SHIRAZY) - Ahmad Yasid; Moh Juhdi (STKIP PGRI SUMENEP, 2020)
Abstract Islam, religion of tolerance and love of peace is one of Habiburrahman El Shirazy’s, it is a study indicating the values ​​of love and tolerance of Islam in the modern public space area. This study used the underlying theory of the values ​​of love and tolerance as well as the role of Islam in modern times that has been developing in the public discourse that in the history of human civilization there are several things that must be understood that humans have the sense to differentiate between humans and other creatures. From this reason humans can do something to explore and explain things that are not known by others. The method that is used in data collection technique is documentation technique, because this study is descriptive qualitative. This study examines several things including the values of love and tolerance because accepting differences is a distinct pleasure for each particular societies in other words, not seeing other people as deviants or enemies but as partner to complement each other by having an equal position and equally valid and valuable as a way of managing life and living life both individually and collectively. Acceptance of differences demands changes in the legal rule in people's lives so that the role of religion in the modern public space area becomes a middle way to build diversity and a nature that must both appreciate and respect one another, this diversity is seen in the portrait of everyday life which then creates peace, and harmony in interacting with all elements of society.